Of those who plan: A meta-analysis of the relationship between human capital and business planning. Issue 2 (April 2019) - Brinckmann, Jan; Dew, Nicholas; Read, Stuart; Mayer-Haug, Katrin; Grichnik, Dietmar
Abstract: Business planning is a popular managerial practice, especially in the SME context. Yet, literature presents diverging perspectives regarding business planning and the role it fulfills for the individuals leading these organizations. To advance research, we focus on evidence regarding factors that determine whether and how individuals engage in business planning. Drawing on human capital concepts and the theory of planned behavior, we scrutinize how education and different prominent work experience types influence business planning behaviors. We use meta-analysis to aggregate data on 8095 observations leading SMEs from 31 independent data sets. We find critical differences in planning behaviors relating to human capital types, as well as to whether individuals engage in substantive planning processes or the specific preparation of a formal business plan. Implications of our findings for research on business planning are discussed.